Public Participation In Planning: A Case Study Of Subang Jaya - Nordin, Nikmatul Adha (2011)
The practice of involving public in planning has been in place since the birth of modern town in planning in Malaysia. However at that time, public involvement was only restricted only after a draft plan is completed. The modern planning Act, ie the Town and Country Planning Act 1976 has given a new dimensions in urban planning practice in Malaysia. Throughout the many amendments that had been taking place since 1976 right up to 2001, the Act has improvised the ways of improving the urban planning practice as a whole which includes a more systematic approach on how to involve the public in urban planning process more effectively.